Operative vaginal delivery and invasive procedures in pregnancy among women living with HIV. (March 2017) - Peters, Helen; Francis, Kate; Harding, Kate; Tookey, Pat A.; Thorne, Claire
Abstract: Objectives: To describe the use and outcomes of operative delivery and invasive procedures in pregnancy amongst women living with HIV. Study design: The National Study of HIV in Pregnancy and Childhood (NSHPC) is a comprehensive population-based surveillance study in the UK and Ireland. The NSHPC has collected data on operative delivery since 2008, and invasive procedures in pregnancy (amniocentesis, cordocentesis, chorionic villus sampling) from 2012. Descriptive analyses were conducted on 278 pregnancies expected to deliver from 1 January 2008 with outcome reported to the NSHPC by 31 March 2016. Results: Among 9372 pregnancies in 2008–2016, there were 9072 livebirths with 251 operative deliveries and 27 invasive procedures in pregnancy reported. Information was available for 3023/3490 vaginal deliveries, and use of forceps or vacuum reported in 251deliveries (8.2%), increasing over calendar time to almost 10% by 2014–16. Forceps were used twice as often as vacuum delivery, and forceps use increased over time. One infant delivered operatively is known to have acquired HIV. From 2012 there were 4063 pregnancies resulting in 3952 livebirths, 83 terminations and 28 stillbirths. 2163/4063 had information on use (or not) of invasive procedures in pregnancy. Amniocentesis was reported in 25/2163 pregnancies, there was one report of chorionic villus sampling and one of cordocentesis. There were no reported transmissions following invasive procedures in pregnancy. Conclusions: This is the largest study to date to report on operative delivery in women living with HIV on combined antiretroviral therapy (cART), and provides an up-to-date picture of invasive procedures during pregnancy in this group. Findings from this comprehensive national study are reassuring but numbers are currently low; on-going monitoring is crucial as obstetric care of women with HIV becomes normalised.